Wastewater and Waste Treatment (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The aim of this reprint is to present current trends and future perspectives in wastewater and waste treatment methods, including economic and environmental assessments. Topics include, but are not limited to, the following:Novel biological, advanced oxidation, and physicochemical wastewater and waste treatment methods;Current trends in wastewater and waste treatment systems;High-environmental-impact waste streams and treatment challenges;The environmental and economic impacts of wastewater and waste treatment methods.